Magnitude and factors associated with upper respiratory tract infection among under-five children in public health institutions of Aksum town, Tigray, Northern Ethiopia: an institutional based cross-sectional study - Zeru, Teklay (Pan Afr Med J, 2020)
INTRODUCTION: upper respiratory tract infection is a leading cause of morbidity among under-five, particularly in the developing countries. Delays in the identification and treatment of under-fives are among the main contributors to the complication. The aim of this study was to assess the magnitude and to identify factors associated with upper respiratory tract infection among under-five children, in public health institutions of Aksum City, Tigray Region, North Ethiopia, 2016. METHODS: institutional based cross-sectional study was done. Cases were under-five children who had get service. The study participants were selected using Systematic random sampling technique. Data were entered, using Epi-info version 7 and analyzed using SPSS version 22.0. Clinical data from the chart were used to diagnose upper respiratory tract infection types. The binary logistic regression model was used to test the association between dependent and independent variables and multivariable logistic regression was used to identify the associated factors to upper respiratory tract infections. RESULTS: out of 213 study participants 52.6% identified as having at least one type of upper respiratory tract infection, i.e. sinusitis 22 (10.3%), 37 (17.4%) otitis media, 39 (18.3%) tonsillitis and common cold 83 (39.0%). Multivariable logistic regression analysis shows that rural residence 7.6 [AOR (95%CI) (2.49, 23.58)], civil servant father's children 4.49 [AOR (95%CI) (1.57, 12.83)], non-immunization 6.0 [AOR(95%CI) (1.38, 26.8)], mud house wall 4.58 [AOR (95%CI) (1.74, 12.0)], rental house 5.1 [AOC (95% CI) (1.82, 14.6] and large family size 5.3 [AOC (95%CI) (2.3, 12.1 )], were found to be statistically associated. CONCLUSION: socioeconomic, maternal and environmental factors had contributed to the upper respiratory tract infection. Strengthening of the existing disease prevention policy as well as improvement of institutional health service behavior is crucial.